2015
DOI: 10.1016/j.cell.2015.08.059
|View full text |Cite|
|
Sign up to set email alerts
|

Regulators of Gut Motility Revealed by a Gnotobiotic Model of Diet-Microbiome Interactions Related to Travel

Abstract: SUMMARY To understand how different diets, the consumers’ gut microbiota and the enteric nervous system (ENS) interact to regulate gut motility, we developed a gnotobiotic mouse model that mimics short-term dietary changes that happen when humans are traveling to places with different culinary traditions. Studying animals transplanted with the microbiota from humans representing each cuisine and fed a sequence of diets representing those of all donors, we find that correlations between bacterial species abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 54 publications
3
151
1
1
Order By: Relevance
“…Whilst the contribution of enteric aganglionosis to HSCR is unquestionable, our findings raise the possibility that, if the epithelial expression of Ret is conserved in humans, dysregulation of epithelial signalling may contribute to disorders that, like HSCR, result from Ret mutation. Epithelial Ret signalling might also contribute to other aspects of gastrointestinal physiology previously shown to be affected by reduced Ret function, such as intestinal motility, gut–microbiota interactions and the compensatory response to massive small bowel resection (Gianino et al , 2003; Hitch et al , 2012; Dey et al , 2015). Interestingly, HSCR is typically diagnosed around birth due to defects in gastrointestinal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the contribution of enteric aganglionosis to HSCR is unquestionable, our findings raise the possibility that, if the epithelial expression of Ret is conserved in humans, dysregulation of epithelial signalling may contribute to disorders that, like HSCR, result from Ret mutation. Epithelial Ret signalling might also contribute to other aspects of gastrointestinal physiology previously shown to be affected by reduced Ret function, such as intestinal motility, gut–microbiota interactions and the compensatory response to massive small bowel resection (Gianino et al , 2003; Hitch et al , 2012; Dey et al , 2015). Interestingly, HSCR is typically diagnosed around birth due to defects in gastrointestinal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in these constituents of the intestinal ecosystem regulate the microbiota composition, which in turn regulates GI motility. It was recently shown that the microbiota can regulate host physiology (57). Elimination of the microbiota caused dilatation of the cecum as a result of abnormal motility that returned to normal upon recolonization with bacteria (58), and it has been proposed that the mechanism underlying this involves regulation by the microbiota of Toll-like receptor expression in the intestine (59).…”
Section: Discussionmentioning
confidence: 99%
“…Strong support for microbial effects on the ENS comes from studies in germ free mice, since these animals have altered motility and changes in ENS structure including fewer myenteric neurons, an increased proportion of NO neurons, and fewer calbindin+ myenteric neurons compared to specific pathogen free or conventionally colonized animals (Collins et al, 2014; Dey et al, 2015; McVey Neufeld et al, 2015). The mechanisms underlying these observations are likely to be complicated.…”
Section: Evidence That Non-genetic Factors May Alter Ens Structure Wimentioning
confidence: 99%